GERAKAN FUNDAMENTALISME ISLAM DI INDONESIA: Perspektif Sosio-Historis - Nor Huda (Fakultas Adab dan Humaniora UIN Raden Fatah, 2016)
Discourse of Islamic thought in Indonesia is evolving as the dynamics of Islamic thought in the Muslim world. One is the Islamic fundamentalist movements that emerged in the Middle East. This movement also affected in Islamic movements in Indonesia. However, within certain limits, Indonesian Islamic fundamentalist movements differ from similar movements in the Middle East. Movement of Islamic fundamentalism in Indonesia merely wish that God's laws are upheld and enforced in this country. Meanwhile, in the Middle East, this movement has been involved in politics far enough. Apparently, the movement of Islamic fundamentalism in Indonesia is not always synonymous with radicalism, like the case of Prosperous Justice Party (Partai Keadilan Sejahtera [PKS]). Through revolution Prosperous Justice Party (Partai Keadilan Sejahtera [PKS]) mind trying to introduce Islamic fundamentalist movements in a way that is more lenient and polite. Keywords: -fundamentalism movement, -mind revolution, - Prosperous Justice Party